Influences of macroeconomic factors on non-performing loan of non-banking financial institutions of Bangladesh: study on IPDC Finance Ltd. - Sarkar, Mahin Uddin (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.